COMPARATIVE ANALYSIS OF PURCHASE DECISIONS BETWEEN ARABIANS KEBAB AND KEBAB TURKEY BABA RAFI FROM VARIANTS OF PRODUCTS AND TASTE - Maryam, Siti; Rahmawati, Annisa; Istiqomah, Istiqomah (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
Culinary business faces competitive competition, especially the company as a producer. Business actors must be careful in determining the marketing strategy of their products so that they become the choice of consumers in making purchases. This study aims to test. This study aims to determine and explain the comparative analysis of purchasing decisions between Arabians Kebab and Kebab Turki Baba Rafi in terms of product variants and taste. The research sample was 100 consumers with accidental sampling technique with the independent t test method. The results of this study are the variables of purchasing decisions, product variants, taste, there are significant differences between the Arabian kebab and kebab baba Rafi. Keywords: product variants, taste, purchasing decisions